Whole genome sequence association analyses of brain volumes in the TOPMed program: Genetics: Genetics of cognitive aging, other dementia, and endophenotypes. (7th December 2020) - Sarnowski, Chloé; Satizabal, Claudia L.; Yanek, Lisa R.; Bis, Joshua C.; Smith, Jennifer A; DeCarli, Charles; Arnett, Donna K.; Psaty, Bruce M.; Nyquist, Paul; Mathias, Rasika A.; Destefano, Anita L.; Seshadri, Sudha; et al.
Abstract: Background: Genome‐wide association studies (GWAS) of brain volumes have identified common genetic variants with modest effect sizes that lie mainly in non‐coding regions. We sought to identify low frequency and rare variants influencing brain volumes by performing whole genome association analyses using sequence data from the Trans‐Omics for Precision Medicine (TOPMed) Program. Methods: We analyzed up to 3, 975 participants (58% women; 78% Europeans, 22% African‐Americans), mean age of 62.5 (13.9), from four TOPMed population‐ or family‐based studies (FHS, GENESTAR, CHS, and GENOA). We excluded participants with dementia, stroke, presence of large brain infarcts, tumor or any other finding affecting the scan. We tested the association of hippocampal (HV), total brain (TBV), lateral ventricular (LVV) and intracranial (ICV) volumes with individual genetic variants using mixed‐effect linear regression models adjusted for age, age 2, sex, study and principal components. Models including HV, TBV and LVV were adjusted for ICV. We accounted for relatedness using a kinship matrix and trait variance variability using a random effects model. We retained variants with a minor allele count greater than 40. Results: We detected new genome‐wide significant (P < 5 × 10 −8 ) low frequency or rare variants in five regions associated with HV (5q31, P  = 10 −9 ) and TBV (2p22, P  = 10 −8 ; 17q25, P  = 4 × 10 −9 ; Xp11, P  = 2 × 10 −10 ; Xq21, P  = 4 × 10 −8 ). We also confirmed previously observed common variants in GWAS loci for HV (12q14 & 12q24), LVV (3q28, 12q23 & 16q24) and ICV (6q21, 6q22 & 17q21). The top 5q31 hit for HV (rs246587) lies at 19kb from the PCDHAC2 gene, encoding neural cadherin‐like cell adhesion proteins that most likely play a critical role in the establishment and maintenance of specific neuronal connections in the brain. Conclusions: Our whole genome analysis revealed intriguing new loci associated with brain volumes. Future work will include ancestry‐specific and conditional analyses, gene‐based and burden tests as well as the inclusion of additional TOPMed cohorts. Supported by: U01s AG058589, AG052409, R01s AG054076, AG033040 AG049607, HL112064, NS062059, FHS contracts HHSN268201500001I and 75N92019D00031, R01HL131136 (Analysis Commons).